Bioinspired materials: From living systems to new concepts in materials chemistry - Böhm, Corinna; Harris, Joseph; Schodder, Philipp; Wolf, Stephan (Materials, 2019)
Nature successfully employs inorganic solid-state materials (i.e., biominerals) and hierarchical composites as sensing elements, weapons, tools, and shelters. Optimized over hundreds of millions of years under evolutionary pressure, these materials are exceptionally well adapted to the specifications of the functions that they perform. As such, they serve today as an extensive library of engineering solutions. Key to their design is the interplay between components across length scales. This hierarchical design-a hallmark of biogenic materials-creates emergent functionality not present in the individual constituents and, moreover, confers a distinctly increased functional density, i.e., less material is needed to provide the same performance. The latter aspect is of special importance today, as climate change drives the need for the sustainable and energy-efficient production of materials. Made from mundane materials, these bioceramics act as blueprints for new concepts in the synthesis and morphosynthesis of multifunctional hierarchical materials under mild conditions. In this review, which also may serve as an introductory guide for those entering this field, we demonstrate how the pursuit of studying biomineralization transforms and enlarges our view on solid-state material design and synthesis, and how bioinspiration may allow us to overcome both conceptual and technical boundaries.
CRIS-Team Scopus Importer:2019-07-23
Keywords: Biomimetic materials; Biominerals; Emergence; Non-classical crystallization